Microcredit as a strategy for poverty reduction: a case study of the Sudan - Eisa, Garout Suliman (David Publishing Company., 2013)
Sudan is among those developing countries characterized by high incidence of poverty in spite of its prodigious resource endowments. Sudan government has continued to introduce progra mmes aiming at alleviation of poverty which were generally characterized by a lack of effec tiveness. The traditional approach towards poverty reduction centered on national development progr ammes designed to enhanc e economic growth and improve standards of living. In addition, the Islamic institution of Zakat was utilized to help poor families start income-generating projects. However, recently, a more ambitious poverty-focused microcred it programme was la id forth. Thus, billions of dollars were earmarked for microcredit to help the poor obtain investible resources which can be directed towards starting income-generating projects. This paper argue s that today, there is no shortage of funds earmarked for microfinance in Sudan. But the prevailing institutional inadequacies would not allow such substantial outlays to have much impact on poverty reduction. This paper revi ews the history of microcredit and microfinance in the country, highlights the roles of different institutions in provision of microcredi t, attempts to figure out its possible policy outputs, and finally makes some sugges tions to overcome the evident shortcomings.